Gender and Moral Decadence in Careers - Hidayatullah Ismail; Fitriani Asri; Herlina (Global Action and Education for Society, 2026)
In relation to the issue of the relationship between men and women and the capacity of humans as servants of Allah swt, there is no difference between them. The basic principles of the Quran reveal a reality of egalitarian views. Both living beings have the same potential and opportunity to become ideal servants. The creation of models and kinship systems within a society requires a long time and historical process, and depends on various factors, including geographical factors. The Quran emphasizes that the most ideal servants are the muttaqun. The phenomenon occurring in the conditions of religious communities and societies gives rise to issues of moral decadence coloring human interactions. In this case, the research focuses on the work environment, specifically the gender career life at STAI Diniyah Pekanbaru, with the research period from February to April 2020. The focus on the decline in moral values is due to free social interactions that do not adhere to ethics and morals. The researcher conducted field research to perform a detailed analysis, using qualitative classification and a descriptive explanatory level. The use of case studies as a type and strategy of discovery in this research. In this study, the main finding is that moral principles serve as the education of a person's soul, keeping it in a state of purity, commendability, and free from disgraceful traits. There is a positive correlation between job level, education level, work routine, and social interactions conducted both inside and outside the campus. The research results from the responses of 37 respondents show a direct correlation in internal and external campus social interactions. The environment plays a significant role in the moral gender shift in careers. In this study, it is argued that a high frequency of meetings, unrestricted and free, can strengthen human relationships with one another. The evidence in this study is that in the workplace, one must uphold good moral principles and Islamic law. Habluminannas, maintaining good relations, and other forms should not be an excuse in a career to open the door to immorality.